The effect of operating capacity and leverage on financial stability: Testing the interaction of coporate governance - Amanda Dwi Damayanti; Erna Listiana; Wendy Wendy; Mustarudin Mustarudin; Uray Ndaru Mustika (Trigin Publisher, 2023)
Financial stability is a picture of the unstable financial condition of a company that can allocate its financial resources to prevent interference with the financial system. This study examines the influence of leverage variables and operational capacity on corporate financial stability in the property and real estate industries, with corporate governance factors as moderation. The data used is the annual Property and Real Estate Companies report on the Indonesian Stock Exchange for 2018-2022. The study involved 91 companies as a population, and 22 samples were taken over a five-year analysis period. Data analysis using panel data regression with E-Views 12 as software. Financial stability is affected positively and significantly by Operational Capacity, while Corporate Governance and Financial Stability are affected negatively and significantly by Leverage. That can explain the importance of financial stability in a company so that it can continue to survive and thrive. This research aims to give readers and stakeholders insight into Financial Stability in the real estate sector, thus minimizing the risk of financial difficulties in a company. Further research needs to add relevant variables and expand research objects.